Sabotaged - Pettrey, Dani (Pettrey, Dani. Alaskan courage., 2015)
"Growing up in Yancey, Alaska, Kirra Jacobs and Reef McKenna were always at odds; now working together to stop an ecoterrorist threatening the Iditarod and Alaskan lives, Kirra and the entire McKenna family attempt to prevent tragedy in this final book of the ALASKAN COURAGE series"--